ANÁLISIS DE DIAGNÓSTICO EN EL MODELO DE REGRESIÓN LOGÍSTICA: UNA APLICACIÓN - Solano Dávíla, Olga (2007)
Logistic regression is a multivariate technique very important for its applications in different areas of knowingness and its applications has been growing more. In clinical and epidemiological research, in particular in a study coronary illness, analysis of logistic regression has been applied for first time around 60 years old (lB) . In studies of logistic regression, it is frequent that a group of observations can be outliers. In the construction of logistic regression models is important to examine the observations to detect the existence of one or more observations that is controlling important properties of the modelo We present a discussion on diagnostic to logistic regression model (5), on factors of risk in illness of bone.